Electrophysiological assessment of radial shock wave therapy for carpal tunnel syndrome - Zong, Ya; Zhang, Hong; Xu, Peipei; Chen, Maoqi; Xie, Qing; Zhou, Ping (Frontiers in Neuroscience, 2023)
This study presents an electrophysiological assessment of radial extracorporeal shock wave therapy on patients with carpal tunnel syndrome (CTS). Sixteen CTS subjects received radial extracorporeal shock wave therapy once a week for five consecutive weeks. Outcome performance was assessed using the Boston Carpal Tunnel Questionnaire (BCTQ) and electrodiagnostic measurements including a nerve conduction study of the median nerve and a compound muscle action potential (CMAP) scan of the abductor pollicis brevis muscle. The BCTQ and the sensory conduction test measurements were all statistically improved after the treatment. However, the motor conduction test measurements were not significantly different before and after the treatment. The CMAP scan examination revealed MScanFit motor unit number estimation (MUNE) was significantly higher after the treatment, while no significant change was found in StairFit MUNE and step index. These results confirmed the effectiveness of shock wave therapy for treating CTS symptoms and the associated sensory property changes. The reasons for the inconsistencies from different CMAP scan processing methods are worthwhile targets for further investigation.